2021
DOI: 10.3389/fimmu.2021.715848
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Attenuates Viral-Induced Inflammation and Fibrotic Responses in Bronchial Smooth Muscle Cells

Abstract: Toll-like receptor 3 (TLR3) activation by viral infections plays a key role in promoting inflammatory immune responses that contribute to pulmonary fibrosis in chronic inflammatory respiratory diseases. Vitamin D3 has been shown to be beneficial to patients with asthma and chronic obstructive pulmonary disease (COPD) through its anti-inflammatory and anti-fibrotic properties. Smooth muscle cells are one of the major contributors to airway remodeling in asthma and COPD. We therefore aimed to investigate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…A significant role of FN1 in anti-inflammatory mechanisms and related diseases has been extensively reported in the literature. [51][52][53] FN1 is highly expressed in nodular disease, a systemic inflammatory disease manifested by pulmonary involvement and erythema nodosum of the skin. [33] CDK2 is involved in cell cycle regulation and is generally considered important in cancer pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A significant role of FN1 in anti-inflammatory mechanisms and related diseases has been extensively reported in the literature. [51][52][53] FN1 is highly expressed in nodular disease, a systemic inflammatory disease manifested by pulmonary involvement and erythema nodosum of the skin. [33] CDK2 is involved in cell cycle regulation and is generally considered important in cancer pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive TLR3-mediated inflammation may play a key role in promoting asthma exacerbation and fibrosis, with bronchial smooth muscle cells (BSMCs) being one of the major contributors to asthma airway remodeling (Yang et al, 2017 ). Plesa et al ( 2021 ) indicate that vitamin D3 can attenuate TLR3 agonist-induced inflammation and fibrotic responses in BSMCs, exerting a protective effect in the development of worsened conditions associated with viral infections. These results support vitamin D3 supplementation in virus-infected asthma patients.…”
Section: The Role Of Gut Microbial Changes Caused By Respiratory Infe...mentioning
confidence: 99%
“…Vitamin D has been shown to reduce proliferation, proinflammatory cytokines, matrix metalloproteinase (MMP) in airway smooth muscle cells [ 32 ], factors contributing to airway inflammation and remodeling. In another study, it was shown that vitamin D in airway smooth muscle cells attenuates TLR3 agonist-induced inflammatory and fibrotic responses by a viral antigen [ 37 ].…”
Section: Vitamin D and Asthmamentioning
confidence: 99%